The Range of Goods at a Retail Chain: The Formation Technology - POPENKOVA, D. K.; NIKISHIN, A. F. (Journal of Advanced Research in Law and Economics; Vol 10 No 6 (2019): JARLE Volume X Issue 6(44) Fall 2019, 2019)
The category management is a relatively new science. Due to this, there is much for researchers to study. In this article the references on approaches to forming the range of goods have been reviewed, the authors’ approach has been shown by using the practical example, and the particular retailer has been given recommendations on changing the range of goods through the example of one of their categories. In this research, the approach to forming the range of goods, based on satisfying the customers’ needs, has been reviewed, and its practical use has been described. For these purposes, four retail chains functioning in the ‘neighborhood store’ format and one small category of goods – flour and baking mixes – have been selected. The market data, customer preferences, and sales data for the A retail chain have been analyzed. The range matrices of the chains under study have been analyzed. Shortcomings and strengths have been identified, and the recommendations for the A chain have been made.